2023
DOI: 10.3390/ani13233709
|View full text |Cite|
|
Sign up to set email alerts
|

The Impact of Phytase and Different Levels of Supplemental Amino Acid Complexed Minerals in Diets of Older Laying Hens

Waleska Medeiros-Ventura,
Carlos Rabello,
Marcos Santos
et al.

Abstract: A study was conducted to evaluate the effects of different sources and levels of supplemental amino acid-complexed minerals (AACM), with and without enzyme phytase (EZ). A total of 512 Dekalb White laying hens at 67 weeks of age were used in a 2 × 3 + 2 factorial arrangement of 8 treatments and 8 replications each. The main effects included EZ supplementation (10,000 FTU kg−1) and AACM inclusion level (100, 70, and 40% of inorganic mineral recommendations), plus 2 control treatments. The group of hens fed AACM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Research has shown that trace minerals bound to nonspecific essential amino acids in a 1:1 ratio can enhance the development of reproductive organs in laying hens ( Pereira et al., 2020 ), increase bone mineralization, and decrease phosphorus (P) excretion in layer-type chickens ( Medeiros-Ventura et al., 2023 ; Ventura et al., 2020 ). They have also been found to improve egg production in laying hens and broiler breeders ( Carvalho et al., 2015 ; Favero et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that trace minerals bound to nonspecific essential amino acids in a 1:1 ratio can enhance the development of reproductive organs in laying hens ( Pereira et al., 2020 ), increase bone mineralization, and decrease phosphorus (P) excretion in layer-type chickens ( Medeiros-Ventura et al., 2023 ; Ventura et al., 2020 ). They have also been found to improve egg production in laying hens and broiler breeders ( Carvalho et al., 2015 ; Favero et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…To allow the original publication to be better understood [ 1 ], the authors would like to make the following updates.…”
mentioning
confidence: 99%